Effectiveness of Counseling and Sound Therapies, Including Mobile Applications and Quran Therapy, in Managing Subjective Tinnitus: randomized controlled trial study - Mohammed, Mohammed Subhan; Zmnako, Sherko Saeed F.; Baban, Muaid Ismaiel Aziz (South Eastern European journal of public health, 2024)
Introduction: Subjective tinnitus, the perception of sound without an external source, affects approximately 15% of the global population. Despite its non-life-threatening nature, tinnitus significantly impacts the quality of life, causing distress, sleep disturbances, anxiety, and depression. Objectives: This study assesses the effectiveness of counseling therapy combined with two sound therapy modalities; mobile applications and Quran therapy in managing tinnitus symptoms. Methods: This randomized controlled trial study involved 270 participants with subjective tinnitus, recruited from a medical center and a private audiology clinic in Sulaymaniyah, Iraq. Participants were divided into two groups: one receiving counseling therapy and sound therapy via mobile applications (ReSound Tinnitus Relief and Beltone Tinnitus Calmer), and the other receiving counseling therapy combined with Quran therapy (Quranic recitation in Maqam Al-Bayati style). Tinnitus severity and its impact on quality of life were measured using the Tinnitus Primary Function Questionnaire (TPFQ-CK) and the Tinnitus Handicap Questionnaire (THQ-CK) before and six months after the intervention. Results: Both therapy groups showed significant improvements in tinnitus severity and quality of life. The TPFQ-CK total scores decreased from 38.18 to 14.99 in the Quran therapy group and from 38.34 to 17.82 in the mobile application group. The THQ-CK total scores decreased from 43.46 to 22.99 in the Quran therapy group and from 43.74 to 25.25 in the mobile application group. Significant reductions were also observed in tinnitus annoyance and loudness levels. Conclusions: Counseling therapy combined with sound therapy, whether through mobile applications or Quranic recitation, effectively reduces tinnitus severity and improves the quality of life for individuals with subjective tinnitus. Quran therapy, leveraging spiritual and cultural practices, showed a slight edge in effectiveness over mobile applications, suggesting that culturally relevant and accessible sound therapy options can enhance tinnitus management.